Cesarean Scar Ectopic Pregnancy: Diagnosis With Ultrasound - Taryn Hoffman; Judy Lin (Clinical Practice and Cases in Emergency Medicine, 2020)
We present a rare case of cesarean scar ectopic pregnancy as diagnosed by transvaginal ultrasonography. Cases such as this are rare, but they are becoming more commonly detected with the growing frequency of cesarean sections, improving technology, and provider proficiency with point-of-care ultrasound. Quick identification of this dangerous diagnosis can be life saving for the patient, as the outcomes of ruptured cesarean ectopic pregnancy may include significant hemorrhage, uterine rupture, and possibly maternal death.